2012
DOI: 10.1104/pp.111.189605
|View full text |Cite
|
Sign up to set email alerts
|

The TGB1 Movement Protein ofPotato virus XReorganizes Actin and Endomembranes into the X-Body, a Viral Replication Factory  

Abstract: Potato virus X (PVX) requires three virally encoded proteins, the triple gene block (TGB), for movement between cells. TGB1 is a multifunctional protein that suppresses host gene silencing and moves from cell to cell through plasmodesmata, while TGB2 and TGB3 are membrane-spanning proteins associated with endoplasmic reticulum-derived granular vesicles. Here, we show that TGB1 organizes the PVX “X-body,” a virally induced inclusion structure, by remodeling host actin and endomembranes (endoplasmic reticulum an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
159
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 119 publications
(180 citation statements)
references
References 74 publications
(155 reference statements)
13
159
0
1
Order By: Relevance
“…Pumilio-based RNA imaging has enabled subcellular detection of the mRNAs of mitochondrial NADH dehydrogenase and -actin, as well as retroviral RNA in mammalian cultured cells (20)(21)(22)(23), and of the genomes of Tobacco mosaic virus, Potato virus X and Turnip mosaic virus in live plant tissue (24)(25)(26)(27). Of particular relevance to the topic of this volume, Pumilio-based RNA imaging has recently shown that Potato virus X is present in membrane structures at the entrances of plasmodesmata that also contain the viral replicase (27).…”
Section: Rna-binding Domain Of Pumilio Proteinsmentioning
confidence: 99%
See 4 more Smart Citations
“…Pumilio-based RNA imaging has enabled subcellular detection of the mRNAs of mitochondrial NADH dehydrogenase and -actin, as well as retroviral RNA in mammalian cultured cells (20)(21)(22)(23), and of the genomes of Tobacco mosaic virus, Potato virus X and Turnip mosaic virus in live plant tissue (24)(25)(26)(27). Of particular relevance to the topic of this volume, Pumilio-based RNA imaging has recently shown that Potato virus X is present in membrane structures at the entrances of plasmodesmata that also contain the viral replicase (27).…”
Section: Rna-binding Domain Of Pumilio Proteinsmentioning
confidence: 99%
“…This principle is the only form of Pumilio-based RNA imaging so far applied in plants ( [24][25][26][27].…”
Section: Choice Of Reporter Systemmentioning
confidence: 99%
See 3 more Smart Citations